Under the skin of a culture: perceptions of fake leopard skin alternatives in the Shembe Baptist Church - Mabaso, Xolani X (Department of Biological Sciences, 2025)
Since prehistoric times, big cats such as leopards have had symbolic importance in human culture. They are prized as symbols of power, nobility, ferocity and very often, masculinity. Religious groups have also been known to wear animal skin as part of their ceremonial regalia, typically for aesthetic, superstitious and spiritual reasons. However, throughout much of their historical distribution, leopards have been actively hunted, poached or killed in retaliation for livestock losses so extensively that many of their populations are now under direct threat. Despite attempts to control illegal harvesting and trade through international conservation organizations such as CITES the use of and trade in leopard products remains commonplace throughout their range. In Southern Africa one of the most widespread and obvious users of leopard skins are members of the Shembe Nazareth Baptist Church. The Shembe church, which has approximately 6 million followers, was founded by Prophet Isaiah Shembe on 1910 in Durban, South Africa. This modern take on Zionist beliefs integrates aspects of Christianity and traditional Zulu beliefs. Followers wear white, full length garments when praying and a diverse array of animal skins when engaging in traditional dance. The most popular and prestigious animal skin is that of a leopard. Given concerns around the increasing demand for leopard skins, Panthera (cat conservation NGO) initiated the Furs for Life project in 2013, introducing synthetic leopard skin alternatives to real skins. These ‘faux' skins were donated to the Shembe church for dissemination among their followers, with the hope that this would ultimately reduce demand for real skins. While approximately 24,000 faux furs have been distributed within the Shembe church to date, little is known about how well these have been received or how effective this conservation intervention has been. In this brief, exploratory study 100 randomly selected recipients of faux furs were surveyed to address concerns pertaining to: faux fur use, demand for real skins, consumer satisfaction, knowledge of conservation and policy perceptions, through a descriptive statistics and basic generalised linear model framework. We found that after a period of three years, at least 90% of the respondents still have their fake furs, have been using them approximately six times a year and were positive about the product they received from Panthera. More than 60% of respondents are aware of leopard population trends, and 66% of respondents believed that the government should intervene in leopard conservation. Faux leopard furs have been very successful, reporting a higher than 50% usage in Shembe gatherings, with most respondents indicating how aesthetic and durable faux furs are as well as how similar they are to real leopard fur. As this was a pilot study with only 100 respondents so statistical power was limited given the number of variables, we suggest a similar study done on a larger scale to understand the efficacy of the intervention.